2014
DOI: 10.1007/s10725-014-0006-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of PaPYLs, PaPP2Cs and PaSnRK2s during sweet cherry fruit development and in response to abscisic acid and auxin at onset of fruit ripening

Abstract: To further understand the basis of abscisic acid (ABA) signal transduction in regulating sweet cherry fruit development and ripening, and also the interaction between ABA and indole acetic acid (IAA) at the onset of fruit ripening, full-length or partial cDNA of three PaPYLs (ABA receptor), six PaPP2Cs (type 2C protein phosphatase) and six PaSnRK2s (subfamily 2 of SNF1-related kinases) were identified from sweet cherry. Multiple alignments and phylogeny analyses showed that most of the functional residues or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 39 publications
3
45
2
Order By: Relevance
“…4 ). Three ABA receptor genes ( PYLs ), six 2C protein phosphatases ( PP2Cs ), and six subfamily 2 SNF1-related kinases ( SnRK2 s) were previously cloned from cherry fruits ( Wang et al , 2015 ). Of these, PacPYL2, PacPP2C3 , and PacSnRK2.3 were strongly expressed in sweet cherry fruits during ripening, but expression of the other genes was very low.…”
Section: Resultsmentioning
confidence: 99%
“…4 ). Three ABA receptor genes ( PYLs ), six 2C protein phosphatases ( PP2Cs ), and six subfamily 2 SNF1-related kinases ( SnRK2 s) were previously cloned from cherry fruits ( Wang et al , 2015 ). Of these, PacPYL2, PacPP2C3 , and PacSnRK2.3 were strongly expressed in sweet cherry fruits during ripening, but expression of the other genes was very low.…”
Section: Resultsmentioning
confidence: 99%
“…ABA is a broad-spectrum phytohormone involved in the regulation of stomatal opening, growth and development, and coordination of various stress signal transduction pathways during abiotic stress [16,17]. To date, several ABA-pathway genes responsible for plant tolerance to abiotic stress have been identified, including the ABA receptor PYL8/RCAR3 and the regulatory factors SNF1 (SNF1-activated protein kinase) and PP2C (2C protein phosphatases) [18][19][20][21]. Moreover, it has been reported that ABA is associated with the sugar response pathway in plants [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that high concentrations of abscisic acid (ABA) are required for ripening in sweet cherries ( Luo et al, 2013 ; Wang et al, 2015 ). ABA is a sesquiterpenoid hormone, derived from carotenoids, that is implicated in several physiological processes, from seed dormancy to senescence processes, including plant stress responses and the regulation of fruit development ( Nambara and Marion-Poll, 2005 ; Finkelstein, 2013 ; Leng et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%